Deculturalisation Trajectory of the South African Early Childhood Development Centres: Parents’ Voices - Mkhomi, Moses Sipho; Skota-Dayile, Nomvuyo (Edukasi, 2025)
Traditionally, family sociocultural values are core to childcaring and rearing, crucial and a necessity for children’s cognitive development, growth, and learning; thus, this qualitative study sought views of parents on the sociocultural development of their 0-4-year-old children attending ECD centres/preschools/ECD Centres, in four ECD centres in the East London District, of the Eastern Cape Province in South Africa (SA). Bronfenbrenner’s (1979) Ecological Systems Theory was used as a theoretical framework to guide this study. The study was located within the Interpretivist paradigm and used a Case study design to explore the topic. Semi-structured interviews were used to collect data, which was analyzed using a thematic approach. Purposive sampling was used to sample fourteen parent participants comprising nine females and one male aged between 25 and 50 years and four grandmothers aged between 55 and 80 years. The research question was, do parents perceive any alignment between home and ECD centres in terms of sociocultural values. The parent participants in this study echoed the importance of family sociocultural values which are ignored and rejected by ECD centres as irrelevant. The study therefor concludes that the ECD centres are perpetuating deculturisation of mainly Black children. The study, therefore, recommends the compulsory use of South African indigenous languages in ECD centres to embed and transmit sociocultural values.